Finite element model updating of dissimilar plate with rivet joint - Rahman, Hammad A.; Khairi, N. D. A.; M. S. M., Sani (IOP Publishing, 2019)
This study focusses on experimental modal analysis (EMA), finite element analysis (FEA) and model updating. The result of FEA and EMA will be validated and analysed. Then, the study extended to the early stage of model updating by assuming that the riveted dissimilar plates is a rigid body instead of two dissimilar plates. These modal parameters are crucial in providing various periods at which it will naturally resonate to avoid the structure continue to resonate and experience structural damage. Modal parameters of the dissimilar plate with rivet joint which include natural frequency and mode shapes were determined through EMA and FEA. Comparison of experimental data and the simulation data reveals a good correlation between the values of natural frequency. Minor discrepancies of the percentage of error between EMA and FEA are acceptable with the percentage of error is within the range of 0.4% to 13%. Furthermore, the conducted model updating able to reduce to an error range of 0.03% to 0.1%. Through this study, the best way of conducting finite element analysis and model updating for dissimilar plate material with rivet joint is also determined.